Quantitatif Risk Assesment (QRA) Paparan Timbal (Pb) Sebagai Upaya Preventif Pada Masyarakat Nelayan Pesisir - Alfina Baharuddin; Yuliati Yuliati; Indasari Indasari; Adira Artika Aulia (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Lead is a heavy metal that is often found in shellfish. Increased lead levels in shellfish are also associated with increasing industrialization. The purpose of this study was to determine the QMR and lead (Pb) exposure concentration among shellfish fishermen in the waters of North Galesong. This study is quantitative in nature, using analytical methods with a cross-sectional approach to determine the factors associated with lead (Pb) exposure in fishermen's hair. The research design is descriptive. The research design used is a cross-sectional study. The research sample consisted of 30 coastal fishermen located in the waters of Galesong Takalar. The sampling method used was purposive sampling. This study showed that the results of the chi-square test obtained a value of p= 0.426 > α (0.05), so it can be concluded that there is no significant relationship between body weight and lead concentration from height at high risk and Pb concentration does not meet the requirements in 1 (20.0%) person and height at high risk and Pb concentration meets the requirements in 4 (80.0%) people with a total of 5 (100%). It can be concluded that there is no relationship between nutritional status, there is a relationship between duration of consumption, and there is no relationship between health complaints. It is hoped that fishermen will increase their awareness in efforts to reduce and pay attention to the duration of shellfish consumption to minimize lead exposure.